Pengamatan Okultasi Beta Scorpio oleh Planit Jupiter - B. Hidajat (Journal of Mathematical and Fundamental Sciences, 1972)
The occultation of the multiple star Beta Scorpio by Jupiter was observed visually and photographically with the 24"-twin telescope of the Bosscha Observatory. The photographic records obtained by S.M. Larson, using the instrument of the Bosscha Observatory, provided support to a scale height greater than 8 km. The Lembang visual measurement is shown to be consistent with other observations, taken from other observatories.